2009
DOI: 10.1016/s1015-9584(09)60016-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis in Surgical Intensive Care Unit: Prevalence and Risk Factors

Abstract: The prevalence of DVT in critically ill patients in a Thai surgical ICU was approximately 10.5%. Further research is needed to evaluate the risks and benefits of venous thromboprophylaxis in Thai patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
3
13
6
Order By: Relevance
“…2005, Muscedere et al. 2007, Wilasrusmee et al. 2009), but was lower than that in other studies (Marik et al.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…2005, Muscedere et al. 2007, Wilasrusmee et al. 2009), but was lower than that in other studies (Marik et al.…”
Section: Discussioncontrasting
confidence: 68%
“…Kim and Brophy (2009) also stated that age >40 years was one of the most commonly identified risk factors. Age was significantly different between DVT‐positive and DVT‐negative surgical Thailand ICU patients in univariate analysis, and the mean age of the subjects was 55 years, younger than the 61·3 years of our subjects (Wilasrusmee et al. 2009).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Compared with patients with 1 d ICU LOS, patients with ICU LOS of 4e10 d had more than twice the odds of developing DVT, and patients with ICU LOS >10 d had more than four times the odds of DVT. Longer ICU stays associated with critical illness or injury have been previously demonstrated to pose a higher risk of VTE in a study of 190 surgical ICU patients by Wilasrusmee et al [18], who reported that the odds of VTE increased by 7% per day in the ICU. The relationship between a long ICU stay and the risk of DVT is multifactorial.…”
Section: Discussionmentioning
confidence: 95%